Analisis Perlindungan Hukum Terhadap Etika Pengambilan Sampel Urin Mahasiswa untuk Isolasi DNA - Dahlan Sitohang; Fitria Diniah Janah Sayekti; Mastuti Widi Lestari (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
Vulnerability to violations of patient rights as research subjects is the background for the formation of an effort to protect humans as research subjects. The purpose of this study is to analyze how Legal Protection is related to the collection of student urine samples in the DNA Isolation context and what ethics must be adhered to in taking student urine samples for DNA isolation at Stikesnasional. The research method uses a normative legal research type by examining various types of materials originating from several laws and regulations. Research involving humans as subjects, such as urine sampling for DNA isolation, must be carried out with strict ethical principles, including voluntary consent (informed consent), protection of data confidentiality, and respect for the dignity and rights of subjects. Researchers are required to ensure that the procedure does not endanger the physical and psychological well-being of the subject and minimize the risks that may arise. All research involving humans must obtain approval from an ethics committee to ensure that the research protocol meets applicable ethical and legal standards.